Study on the Oil Churning Power Loss of External Gear Pump - Tang Jinglai; Deng Bin; Wang Guozhi; Yu Lanying (Jixie chuandong)
The pressure generated by the compression of the trapped oil lead to a resistance moment,which will result in a certain oil churning power losses,when the external gear pump is working. In order to determine this part of losses,a calculation method of the oil churning power losses of external gear pump is presented. The two- dimensional simulation of a certain type of external gear pump is carried out by using dynamic mesh technology of CFD software FLUENT,and the change of the oil churning power losses in a period of the trapped- oil under different revolving speed and working pressure is analyzed. The results indicate that the oil churning power losses are mainly affected by the trapped- oil pressure,and increase along with the revolving speed and working pressure,which account for 0. 43% 5. 26% of the input power.